Targeting autophagy in cancer - Onorati, Angelique V.; Dyczynski, Matheus; Ojha, Rani; Amaravadi, Ravi K. (Cancer, 2018)
Autophagy is a conserved, self‐degradation system that is critical for maintaining cellular homeostasis during stress conditions. Dysregulated autophagy has implications in health and disease. Specifically, in cancer, autophagy plays a dichotomous role by inhibiting tumor initiation but supporting tumor progression. Early results from clinical trials that repurposed hydroxychloroquine for cancer have suggested that autophagy inhibition may be a promising approach for advanced cancers. In this review of the literature, the authors present fundamental advances in the biology of autophagy, approaches to targeting autophagy, the preclinical rationale and clinical experience with hydroxychloroquine in cancer clinical trials, the potential role of autophagy in tumor immunity, and recent developments in next‐generation autophagy inhibitors that have clinical potential. Autophagy is a promising target for drug development in cancer. Cancer 2018. © 2018 American Cancer Society. Autophagy is an emerging target in cancer therapy. This review highlights recent advances in basic understanding of autophagy, results from clinical trials targeting autophagy, and future directions for the field.